A Survey of Content-Oriented Future Communication Network - Qian Hu; Muqing Wu; Song Guo (Dianxin kexue)
With the exposure of many shortcomings in nowadays internet, there have been lots of studies deeply in the future network around academic circles recent years. Amount these studies, establishing a CON（content-oriented network）is one of the representative researches. CON which is attracting many researchers' attention no longer uses the traditional communication mode called “end-to-end”, but focuses on what it transmits. In this paper, we present a comprehensive survey on the key technologies of CON. The study background of CON following with several key technologies including naming, routing, security and cache are introduced. At last we make a prediction on the research focus of future CON and the development direction.